Market Perceptions of Reserve Disclosures under SFAS No. 69 - Clinch, Greg; Magliolo, Joseph (The Accounting Review, 1992)
[Since the late 1970s, oil and gas firms have been required to include (unaudited) estimates of proved reserve quantities and valuations based on these estimates in their financial statements. As defined by the SEC, proved reserves are those that will be produced with "reasonable certainty" under existing economic conditions. In addition, firms must disclose estimated quantities of proved developed reserves, which will be produced from existing wells. At the time the proved reserve determination is made, substantial uncertainty exists as to the amount of oil ultimately recoverable, suggesting that the reserve estimation process is unreliable (Magliolo 1986b). Although certain constituencies have indicated interest in having firms disclose reserve quantities (see, e.g., Deakin and Deitrick 1982), the relevance of the disclosures for any given firm is an open question. It is to this issue that our research is directed. Prior research has demonstrated a weak association between security prices and oil and gas valuation disclosures required by SFAS No. 69 (see, e.g., Harris and Ohlson 1987; Magliolo 1986a). At least two explanations could account for the weak association: (1) reserve quantity estimates underlying the valuation disclosures are unreliable, and (2) the valuation model used to attach value to reserve quantities is flawed. Although the valuation approach used in these "reserve recognition accounting" disclosures has been widely disparaged, much criticism also concerns problems in the estimation of oil and gas reserve quantities. This article narrows the focus of prior research and specifically examines the value-relevance of reserve quantity disclosures required by SFAS No. 69 (FASB 1982). This more narrow focus permits us to investigate, for the first time, one of the explanations for why the reserve valuation components do not appear to be particularly informative. It also allows us to compare the informativeness of management claims about reserve quantities in the SFAS No. 69 disclosures with quantity estimates that we infer from management actions (i.e., production of oil). The article explores two empirical questions concerning reserve quantity disclosures. First, we examine the required SFAS No. 69 disclosures for proved reserves and proved developed reserves and ask whether these reserve estimates are value-relevant, given a benchmark estimate of reserves based on firms' current oil production levels. The second question is whether the association between market valuation and firms' reserve disclosures differs across firms according to characteristics of the disclosed data. Specifically, we determine whether investors' reliance upon SFAS No. 69 reserve quantity disclosures is related to variation in the reliability of such disclosures across firms, as indicated by the absolute size and direction of reserve estimate revisions, as well as the ratio of proved developed to total proved reserves. Each of these factors potentially provides information on the reliability or usefulness of reserve disclosures. In our first tests, which do not allow for firm-specific variation in the informativeness of SFAS No. 69 quantity disclosures, we find no evidence that disclosures based on proved reserves and proved developed reserves provide additional value-relevant information to market participants once production is known. However, when we partition our sample, we find that the proved reserve information is informative for a subset of firms whose reserve quantity estimates appear more reliable. The importance of our results extends beyond the oil and gas accounting area. The differential reliability results represent some of the first capital-markets-based evidence that the informativeness of a disclosure varies in accordance with the accuracy of management projections. Stated differently, our evidence suggests that investor reliance on disclosures varies as a function of their "quality." Also, our initial results that disclosures of proved reserve quantities provide no information once production is known suggest a reliance by investors on the "objective" information provided by management actions (production decisions) rather than the (potentially) subjective estimate of proved reserves.]